Endothelial calpain systems orchestrate myofibroblast differentiation during wound healing. Issue 2 (10th September 2018) - Miyazaki, Takuro; Haraguchi, Shogo; Kim-Kaneyama, Joo-Ri; Miyazaki, Akira
ABSTRACT: The transformation of fibroblasts to myofibroblasts plays a major role in fibrogenic responses during dermal wound healing. We show a contribution of calpain systems (intracellular regulatory protease systems) in vascular endothelial cells (ECs) to myofibroblast differentiation in wound sites. Dermal wound healing experiments in mice found that calpastatin (an endogenous inhibitor of calpains) is enriched in preexisting vessels but not in newly formed capillaries. Transgenic overexpression of calpastatin in ECs delayed wound healing in mice as well as reducing the keratinocyte layer, extracellular matrix deposition, and myofibroblast accumulation in wound sites. EC and leukocyte markers, however, remain unchanged. Calpastatin overexpression reduced the expression of genes encoding platelet‐derived growth factor‐B and PDGF receptor‐β (PDGFR‐β). Topical application of platelet‐derived growth factor‐BB–containing ointment to wounds accelerated healing in control mice, but calpastatin overexpression prevented this acceleration. In cultured human dermal fibroblasts, α‐smooth muscle actin and PDGFR‐β were up‐regulated by coculturing with ECs, but this action was inhibited by suppression of EC calpain activity. EC‐driven transformation of mouse dermal fibroblasts was also suppressed by calpastatin overexpression in ECs. These results suggest that endothelial calpain systems influence PDGFR‐β signaling in fibroblasts, EC‐driven myofibroblast differentiation, and subsequent fibrogenic responses in wounds.—Miyazaki, T., Haraguchi, S., Kim‐Kaneyama, J.‐R., Miyazaki, A. Endothelial calpain systems orchestrate myofibroblast differentiation during wound healing. FASEB J. 33, 2037–2046 (2019). www.fasebj.org